2020
DOI: 10.1159/000507592
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Endobronchial Ultrasound Strain Elastography in Mediastinal Lymph Node Staging: The E-Predict Multicenter Study Results

Abstract: Background: Systematic assessment of lymph node status by endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) is indicated in (suspected) lung cancer. Sampling is herein guided by nodal size and FDG-PET characteristics. Ultrasound strain elastography (SE) might further improve risk stratification. By imaging tissue deformation over time, SE computes relative tissue strain. In several tissues, a lower strain (deformation) has been associated with a higher likelihood of malignancy. Objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 17 publications
0
35
1
Order By: Relevance
“…All patients with a suspected or proven NSCLC in the Radboudumc routinely receive diagnostic and staging work-up according to ACCP and ESTS guidelines and multi-disciplinary team (MDT) decision-making, with the exception being that our pulmonary nodule diagnostic program routinely includes an EBUS evaluation in combination with a navigation bronchoscopy, irrespective of PET/CT findings and despite the limited tumor size in this subgroup [32]. In our routine EBUS staging procedures, all lymph nodes >5 mm short axis are aspirated [33,34]. Our MDT consists out of oncological pulmonologists, thoracic radiologists, pathologists, radiation oncologists and cardiothoracic surgeons, organized in a multidisciplinary team dedicated to lung cancer care [35].…”
Section: Methodsmentioning
confidence: 99%
“…All patients with a suspected or proven NSCLC in the Radboudumc routinely receive diagnostic and staging work-up according to ACCP and ESTS guidelines and multi-disciplinary team (MDT) decision-making, with the exception being that our pulmonary nodule diagnostic program routinely includes an EBUS evaluation in combination with a navigation bronchoscopy, irrespective of PET/CT findings and despite the limited tumor size in this subgroup [32]. In our routine EBUS staging procedures, all lymph nodes >5 mm short axis are aspirated [33,34]. Our MDT consists out of oncological pulmonologists, thoracic radiologists, pathologists, radiation oncologists and cardiothoracic surgeons, organized in a multidisciplinary team dedicated to lung cancer care [35].…”
Section: Methodsmentioning
confidence: 99%
“…Only 2 of the patients were diagnosed with pneumoconiosis before EBUS-E. Although our EBUS-E evaluation criteria were different from those of Verhoeven et al [1], considering the principle of EBUS-E, a patient’s background can greatly influence the strain values on EBUS-E. The LNs in patients with a history of occupational exposure and without a diagnosis of pneumoconiosis may be hardened, and are likely to give false-positive results on EBUS-E.…”
mentioning
confidence: 88%
“…We read the article by Verhoeven et al [1] with great interest and appreciate the authors’ efforts in investigating the diagnostic accuracy rate (DAR) of endobronchial ultrasound elastography (EBUS-E) with strain values (≥115) that can be evaluated in real-time. They showed that DAR increased when size (≥8 mm) and 18 F-fluorodeoxyglucose positron emission tomography (FDG-PET) findings were considered.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thank you for your interest in our work on EBUS strain elastography [1] and for sharing your experience. In our reply, we will discuss the points raised and address several points for clinical application of EBUS strain elastography and for further research with this technology.…”
mentioning
confidence: 99%